(untitled) (International Journal of Engineering and Computer Science, 2015)
These Mobile ad hoc networks (MANETs) are an epitome for instances where a fixed infrastructure is not available or infeasible. Today’s MANETs however, possibly suffer from network partitioning. This kind of constraints makes MANETs illegible for applications such as crisis or catastrophe management and extreme battlefield communications, in which team ought to endeavor in groups scattered in the application territory. In similar applications, intercommunication within the group is vital to the team effort. To address this flaw, we have come up with this paper, a totally new class of ad-hoc network called Mobile Mesh Network. In Contrary to the existing typical mobile-mesh networks, the nodes of an mobile mesh networks can pursue the mesh clients in the application territory, and organize themselves into a network topology which is suitable to assure good connectivity for intra and intergroup both communications. We lay before a distributed or evenly spread client tracking solution to deal with the charismatic nature of client mobility, and present modus operandi for dynamic topology adoption in compliance with the pattern of mobility of the clients. Our imitated results indicate that mobile mesh network is robust against network partitioning and cover the more no of clients compare to the standard wireless network that is here we track the disappeared clients